Talking with children and young people about death and dying - Turner, Mary, 1933- (Jessica Kingsley Publishers, 2006)
Reviews of the first edition. 'Many adults find it hard to talk to children about death. Too often the myth continues that "the kids are okay" and so they are not helped with the pain of bereavement. This workbook gives them an opportunity to air their concerns, and fears. ... [It is] an invaluable aid to anyone caring for a child.'. - www.familyonwards.com 'This is a highly recommendable book as it covers all aspects and "stages" of bereavement and concludes with sections on reminiscing and moving on.'. - European Journal of Psychotherapy, Counselling &